2022
DOI: 10.1021/acs.langmuir.2c00796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Tuning of Aggregated States for Conformation Control of Cyclized Binaphthyl at the Air–Water Interface

Abstract: An air–water interface enables molecular assemblies and conformations to be controlled according to their intrinsic interactions and anisotropic stimuli. The chirality and conformation of binaphthyl derivatives have been controlled by tuning molecular aggregated states in solution. In this study, we have tuned molecular aggregated states of monobinaphthyldurene (MBD) by applying different mechanical stimuli to control the conformation at the air–water interface. Density functional theory calculations indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The conformation of BBD and MBD, where a binaphthyl molecule is cross-linked with durene, can be controlled using mechanical stimuli in soft and well-miscible lipids but not in poorly miscible and hard lipids ( Table 2 ) [ 29 , 30 ]. Because MBD and BBD do not form two-dimensional monolayers but three-dimensional aggregates by themselves, it is assumed that their molecular conformations are moderately dispersed and modified in lipids with better miscibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conformation of BBD and MBD, where a binaphthyl molecule is cross-linked with durene, can be controlled using mechanical stimuli in soft and well-miscible lipids but not in poorly miscible and hard lipids ( Table 2 ) [ 29 , 30 ]. Because MBD and BBD do not form two-dimensional monolayers but three-dimensional aggregates by themselves, it is assumed that their molecular conformations are moderately dispersed and modified in lipids with better miscibility.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular conformations of binaphthyl molecules were also controlled in lipid matrices. M. Ishii et al formed monolayers of MBD [ 30 ], a binaphthyl molecule cross-linked with durene, and its dimer, BBD [ 29 ], mixed with various lipid matrices at the air – water interface and mechanically controlled their molecular conformations ( Figure 7 ). DFT calculations revealed that MBD and BBD have three main conformers: the most stable 1-conformers, 2-conformers with energies of a small kcal mol −1 , and unstable flat conformers.…”
Section: Molecular Machine In Lipid Matrixmentioning
confidence: 99%
“…On the other hand, the molecular aggregation state of monobinaphthyl durene can be tuned by applying different mechanical stimuli to control its conformation at the air-water interface. 118 For example, the molecular conformation and aggregation state of monobinaphthyl durene could be continuously controlled by applying mechanical stimuli such as vortex motion at the air-water interface. These results provide various insights into the regulation of the dynamic behavior of molecular machines driven by mechanical stimuli at the liquid interfaces.…”
Section: Molecular Machines Working At Liquid Interfacesmentioning
confidence: 99%
“…At the air-water interface, it is possible to control the conformation of the target molecule depending on the environment, such as the state of miscibility with the mixed lipid. Similarly, the aggregation state of monobinaphthyl durene molecules was controlled by applying different mechanical stimuli at the air-water interface [ 195 ]. When the vortex LB method [ 196 , 197 ] is applied to the water surface, the molecular aggregation state and conformation of the monobinaphthyl durene molecules depend on the molecular density and vortex flow velocity at the interface.…”
Section: Working On Watermentioning
confidence: 99%